2021
DOI: 10.1038/s42003-021-02447-w
|View full text |Cite
|
Sign up to set email alerts
|

Spectral dynamic causal modelling in healthy women reveals brain connectivity changes along the menstrual cycle

Abstract: Longitudinal menstrual cycle studies allow to investigate the effects of ovarian hormones on brain organization. Here, we use spectral dynamic causal modelling (spDCM) in a triple network model to assess effective connectivity changes along the menstrual cycle within and between the default mode, salience and executive control networks (DMN, SN, and ECN). Sixty healthy young women were scanned three times along their menstrual cycle, during early follicular, pre-ovulatory and mid-luteal phase. Related to estra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
21
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 103 publications
(193 reference statements)
4
21
2
Order By: Relevance
“…Although it is out of the scope of this study, connectivity changes experienced by the placebo group along their menstrual cycle in this study did not completely match changes in healthy naturally cycling women reported in our previous work (52). Although the main reason for these discrepancies may be differences in the time window of each appointment, individual variability in functional responsivity to sex hormones could have also contributed (53).…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Although it is out of the scope of this study, connectivity changes experienced by the placebo group along their menstrual cycle in this study did not completely match changes in healthy naturally cycling women reported in our previous work (52). Although the main reason for these discrepancies may be differences in the time window of each appointment, individual variability in functional responsivity to sex hormones could have also contributed (53).…”
Section: Discussioncontrasting
confidence: 59%
“…Therefore, we find it likely that the constant enhanced synthetic progestins effects, alongside the absence of endogenous hormonal cyclicity and estradiol-progesterone interaction may be of high relevance for the mood side effects and related changes in connectivity here described. Although it is out of the scope of this study, connectivity changes experienced by the placebo group along their menstrual cycle in this study did not completely match changes in healthy naturally cycling women reported in our previous work (52). Although the main reason for these discrepancies may be differences in the time window of each appointment, individual variability in functional responsivity to sex hormones could have also contributed (53).…”
Section: Discussioncontrasting
confidence: 54%
“…Among the multiple cellular components with an intrinsic connectivity and functional networks in the human cerebral cortex (see further discussion in van den Heuvel et al, 2015 ), some large-scale circuits have been studied for their roles in resting state, attention and task-related activity or cognitive functions ( Ng et al, 2016 ; Deming and Koenigs, 2020 ; Forlim et al, 2020 ; Kolb and Whishaw, 2021 ). High signal coherence within these networks makes the sub-components functionally coupled along varied timeframes ( Ng et al, 2016 and references therein), such as in the DMN, which comprises the PC ( Cavanna and Trimble, 2006 ) and the posterior cingulate cortex, the medial prefrontal cortex, and the bilateral intraparietal cortex/angular gyrus; in the “salience network” (SN), including the bilateral anterior insula and the dorsal ACC; and, in the “executive control network” (ECN) including the “frontoparietal network” (FPN) composed of bilateral middle frontal gyri and supramarginal gyri/inferior parietal lobe ( Hidalgo-Lopez et al, 2021 and references therein), the intraparietal sulcus, and dorsal prefrontal cortex ( Ptak, 2012 ; Deming and Koenigs, 2020 ). The PC was also included in the ECN/frontoparietal control system for moment-to-moment tasks ( Kolb and Whishaw, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…From this perspective, dendritic spines are sexually dimorphic and/or affected by gonadal steroids (Woolley and McEwen, 1993 ; Rasia-Filho et al, 2012 ; Luine and Frankfurt, 2020 ), sexual experience and motherhood (Rasia-Filho et al, 2004 ; Zancan et al, 2018 ). These phenomena are relevant to sexual differentiation in healthy brain connectivity and as a biological variable in neuropsychiatric research (Joel and McCarthy, 2017 ; Rubinow and Schmidt, 2019 ; Arnold, 2020 ; Hidalgo-Lopez et al, 2021 ).…”
Section: Brain Network Cellular Connectivity and The Relevance Of Den...mentioning
confidence: 99%